2022
DOI: 10.1097/ico.0000000000003057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Povidone-Iodine Exposure on Corneal Epithelium and Impact on Donor Rim Cultures

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Extensive research has shown that additional tissue warming at eye banks or regional warmer temperature could contribute to increased fungal bioburden in corneal transplants grafts. 9,14,15 Therefore, our research further reduces the risk and burden on the health care system by indirectly minimizing the risk of fungal contamination. In summary, our findings show that corneal endothelium viability assay using trypan blue dye is a more accurate, easy to perform, and extremely timeefficient method compared with specular microscopy after DMEK graft preparation.…”
Section: Discussionmentioning
confidence: 95%
“…Extensive research has shown that additional tissue warming at eye banks or regional warmer temperature could contribute to increased fungal bioburden in corneal transplants grafts. 9,14,15 Therefore, our research further reduces the risk and burden on the health care system by indirectly minimizing the risk of fungal contamination. In summary, our findings show that corneal endothelium viability assay using trypan blue dye is a more accurate, easy to perform, and extremely timeefficient method compared with specular microscopy after DMEK graft preparation.…”
Section: Discussionmentioning
confidence: 95%